Idealizing or Critical? Nostalgia for the Edwardian Golden Age - Sylwia Janina Wojciechowska (Polish Journal of English Studies, 2022)
The myth of the Golden Age found in 20th-century British prose fiction and, particularly, in accounts of the Edwardian decade, seems from the current perspective to be a nostalgically envisioned idyllic haven. Suggestive of peace, innocence, and prosperity, the myth of the Golden Age features in literary renditions of a pre-WWI world, with the works of Kenneth Grahame being a notable example. In stories aimed at younger readers, and in adult fiction too, war – and particularly WWI – constitutes a caesura at which the playful agon of the Edwardian Golden Age transforms into a life-and-death struggle; by the same token, it dramatically severs the nostalgically recalled visions of peace and security. In the paper, I first focus on defining the mythical and the nostalgic. I argue that, exposed through the workings of nostalgia, the notion of war becomes a pivot upon which the myth of the golden-age of Edwardian England is constructed and preserved in the collective memory. Furthermore, I argue that British literature includes literary examples which, paradoxically, both re-enforce and yet simultaneously challenge the golden-age traits of the Edwardian decade. In Kenneth Grahame’s The Golden Age and Dream Days the golden past is perpetuated and firmly cemented, whereas in Siegfried Sassoon’s autobiographical fiction as well as L. P. Hartley’s The Go-Between the initial reminiscences of an idyllic pre-WWI countryside are subsequently questioned. In these texts, the retrospective viewpoint helps investigate the links between myth and nostalgia, which ultimately culminates in a critical message: while deploying the “gilded” images and established rhetoric Sassoon and Hartley challenge the myth of the Golden Age and expose the reality of the Edwardian era.